Catalytically Active Carbon From Cattail Fibers for Electrochemical Reduction Reaction - Liu, Yanyan; Hu, Meifang; Xu, Wei; Wu, Xianli; Jiang, Jianchun (Frontiers in Chemistry, 2019)
Catalytically active carbons derived from plant biomass are conducive to the construction of renewable energy source system and utilization of sustainable resources. In this article, natural cattail fibers are used to fabricate porous nitrogen-doped carbon via direct chemical activation and heteroatom modification treatments. The graphene-like sheets from biomass pyrolysis are assembled into three-dimensional carbon frameworks. The chemical activation of KHCO3 generated unique porous structure and N-containing molecules pyrolysis modification provided nitrogen doping atoms. High surface area up to 2345 m2•g–1 with simultaneous hierarchical pores (from micro to meso and macro) with abundant edge defects are achieved for these carbon materials. These materials have a very large external surface area up to 1773 m2•g–1. The above strategy exhibits a significant synergistic effect on the improvement of catalytic properties toward hydrogen evolution reaction and oxygen reduction reaction. The small over potentials and Tafel slopes of these catalytically active carbons demonstrate excellent potential applications in renewable energy conversion and storage systems. This research established a new link among environmental improvement, biomass conversion and renewable energy utilization.